Radio Days: media-politics in Indonesia - Sen, Krishna (Oxford University Press, 2003)
In the recent excitement about the democratising potential of the 'new' electronic media, theorists have largely ignored the role of the oldest of the electronic 'mass' media, that is, radio. This paper suggests several parallels between the oldest and the newest electronic media in the transmission of anti-authoritarian politics in Indonesia. While the Internet aided sections of the civil society in subverting the state's control over public discourse, in the post-authoritarian politics, radio may remain by far the more significant technology of democratisation. Radio's importance is only in part explained by the economic limits on the distribution of the Internet in Indonesia. We need to look at the particular tessellation of culture, politics and technology in Indonesia to understand the role of radio in the articulation of local politics, in a democratisation process whose success depends on the politics of ethno-cultural decentralisation and devolution of power from urban elites.